1975
DOI: 10.1073/pnas.72.2.604
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of somatomedin titers of normal and hypopituitary sera by addition of L-triiodothyronone in vitro at physiological concentrations.

Abstract: Somatomedin potencies of sera were assayed by following sulfation of mucopolysaccharides in chick embryo sterna in vitro. Apparent potencies of sera from hypophysectomized rats, maintained on a low-iodine diet, were restored to levels above normal by addition to the incubation medium of L-triiodothyronine at 10-7 mol/liter of serum. The potencies of normal rat, human, and fetal calf sera were raised 1.3-to 3-fold by addition of triiodothyronine at 10-9-10-7 mol/liter of serum. L-Thyroxine was about 10 times le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Since hypophysectomized rats and Snell dwarf mice are deficient in pituitary hormones, some of which appear necessary, at least in chick cartilage (Audhya and Gibson 1975), for full expression of somatomedin activity, the interpretation of data concerned with factors controlling growth of these animals may be equivocal.…”
Section: Discussionmentioning
confidence: 95%
“…Since hypophysectomized rats and Snell dwarf mice are deficient in pituitary hormones, some of which appear necessary, at least in chick cartilage (Audhya and Gibson 1975), for full expression of somatomedin activity, the interpretation of data concerned with factors controlling growth of these animals may be equivocal.…”
Section: Discussionmentioning
confidence: 95%
“…Thyroid hormones have been reported to have no effect on mammalian cartilage in vitro (9). In contrast, several in vitro studies show that thyroid hormones stimulate proteoglycan synthesis and potentiate somatomedin action in embryonic chick cartilage (7,8).…”
Section: ¶1~~~~~~~~~~~~~0mentioning
confidence: 99%
“…Changes in thyroid function in vivo lead to alterations in the secretion of many other hormones and some investigators have proposed that those alterations are responsible for the changes in osseous development (5,6). Although thyroid hormones have been shown to stimulate proteoglycan synthesis in vitro, in embryonic chick cartilage (7,8), no in vitro effects of thyroid hormones on mammalian cartilage have been demonstrated (9).…”
Section: Introductionmentioning
confidence: 99%
“…This could result from either relative resistance of Sm producing tissues to the action of GH or from direct inhibition of Sm synthesis or secretion. Alternatively, hypothyroid-induced growth failure may be independent of the GH-Sm axis since in uitro studies have shown that thyroid hormone stimulates indices of growth in cartilage explants (Audhya & Gibson, 1975;Froesch et al, 1976;Burch & Lebovitz, 1982). To further clarify these potential mechanisms we studied the regulation of one of the Sm, somatomedin-C (Sm-C), in patients with primary hypothyroidism by measuring G H responses to provocative stimuli, plasma concentrations of immunoreactive Sm-C before and during thyroid hormone therapy, and the plasma Sm-C responses following exogenous GH administration.…”
mentioning
confidence: 99%